Forum Bildverarbeitung 2022 - Längle, Thomas; Heizmann, Michael (KIT Scientific Publishing, 2022)
Image processing combines the disciplines of cameras - image-based sensors - with the processing of the sensor data - the images. From this follows the particular attraction of this field. The conference proceedings at hand of the "Image Processing Forum", which took place on 24.-25.11.2022 in Karlsruhe as a common event of the Karlsruhe Institute of Technology and the Fraunhofer Institute of Optronics, System Technologies and Image Exploitation, contain the articles of the contributions.